O controle dos atos interna corporis no processo legislativo - Rosa, Bruna Borghetti Camara Ferreira (2019)
This paper aims to analyze the review of interna corporis acts in the legislative process including the parliamentary sovereignty and the parliament right to the legislative due process and the possible processes to enforce such right internally, in the parliament, and externally, in the Judicial Power. The research investigates the structure of the process of law; its concept; its substance; its phases; its irregularities and the safeguards created to ensure the smooth flow of the legislative process in the internal rules of the Legislative Houses, Chamber of Deputies e Senado Federal and in the National Congress internal rules common ascertaining that in the performance of the interna corporis acts there are intervention in the institutional relations between Legislative, Executive and Judiciary; and it concludes that: (i) the internal rules give autonomy to the parliamentarian’s participation in the legislative process; (ii) frequently the parliamentarian’s autonomy is mitigated by its own pairs due to the Executive’s direct influence; (iii) the review of the interna corporis acts in the legislative process is limited, because in an ultimate analysis the Legislative Chamber President’s decision is kept; (iv) the external review can be done by Writ of Mandamus initiated by the parliamentarian or by Direct Action of Unconstitutionality; (v) there is an evolution in the Supremo Tribunal Federal’s analysis of the interna corporis acts in the legislative process